Income and Feasibility Analysis of Coffee Farming - Maure, Gerson Hans; Latuan, Emerensiana; Alota, Mariam (JURNAL AGRIBISAINS, 2023)
The coffee plant is a national leading commodity in the plantation sub-sector. Alor Regency as an area with a dry climate, has great potential for the development of coffee plants in East Nusa Tenggara Province. The total area of ​​coffee plantations in 2022 in this area will reach 2118 ha with a bean production of 302.2 tons/year. The research was carried out in Maleipea Village, Alor Selatan District from March to May 2022. The sample was determined using the Slovin formula. The processed data comes from direct interviews with farmers and through publications from the Central Bureau of Statistics and the Food and Agriculture Office of Alor Regency. This study aims to analyze the community’s income and the feasibility of coffee farming in Malaipea Village. The characteristics of the respondents observed in this study were age, gender, education level, length of business, and land area. The results showed that the income of coffee farming in Malaipea Village was Rp. 1,658,324 with an R/C value of ˃ 1, which is 17.79, so coffee farming in Maleipea Village is feasible.